A complex variable boundary element method for two-dimensional steady heat conduction - Yeo, Wei Liang. (2012)
The Complex Variable Boundary Element Method (CVBEM) is just one of the many ways for analysis of a 2-dimensional heat transfer equation. It has been a valuable technique in analysis of problems that satisfy the Laplace’s equation. The report gives a brief summary of the other popular methods and gives the comparison between them. It also provides the theories required to understand the CVBEM. Lastly, there will be 3 examples of using the CVBEM program to solve problems, in which one will be thoroughly evaluated.